Kunst am Automobil : BMW Art Car Collection. (München : BMW AG, 1991)
Calder, Alexander ; Stella, Frank ; Lichtenstein, Roy ; Warhol, Andy ; Rauschenberg, Robert ; Fuchs, Ernst ; Nelson, Michael Jagamara ; Done, Ken ; Kayama, Matazo ; Manrique, César ; Penck, A.R. ; Maurer, Walter
Duits & Engels
boek